EDUCATION OF INORGANIC WASTE PROCESSING INTO HANDICRAFTS WITH CREATIVITY VALUE AT JEGU 1 AND 2 STATE ELEMENTARY SCHOOLS - Ivan Surya Pramana Putra, Kadek Bagus; T Krisna Narayana, Made Gede Bagus; Ginanita Utami, Cokorda Istri Ustana; Nurullita Wardani, Venti; Devi, Ni Kadek Sintya; Oktavia Gama, Adie Wahyudi; Lestara Permana, Gusi Putu (LPPM Univ. Ibn Khaldun Bogor, 2022)
This community service activity provides education to students of Jegu 1 and 2 State Elementary Schools about education on processing inorganic waste into handicrafts with creative value. The author found that there is still a lot of unused inorganic waste in Jegu village and can be used as a craft that can be useful for everyday life. Because there is still a lot of inorganic waste in the village of Jegu, we from the community service group conducted education about 3R (Reduce, Reuse, Recycle) and the practice of making handicrafts from inorganic waste (plastic bottles) such as piggy banks and pencil boxes which were held at Jegu 1 and 2 State Elementary Schools . The purpose of this education is to help utilize inorganic waste in a craft. The method used in this work program is the direct observation and education phase. Through this work program, the author wants the community, especially the students of Jegu 1 and 2 State Elementary Schools to be aware of the dangers of inorganic waste and inorganic waste that can be used as handicrafts with creative value.